2022
DOI: 10.1093/ageing/afac143
|View full text |Cite
|
Sign up to set email alerts
|

The role of resistance exercise training for improving cardiorespiratory fitness in healthy older adults: a systematic review and meta-analysis

Abstract: Background Declines in cardiorespiratory fitness (CRF) and muscle mass are both associated with advancing age and each of these declines is associated with worse health outcomes. Resistance exercise training (RET) has previously been shown to improve muscle mass and function in the older population. If RET is also able to improve CRF, as it has been shown to do in younger populations, it has the potential to improve multiple health outcomes in the expanding older population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 70 publications
1
22
0
Order By: Relevance
“…10 The characteristics of the included studies are described here in the Methods versus the Results section of the final manuscript because they were derived from the previous systematic review with meta-analysis. 10 Briefly, nine studies were conducted in the United States, 17,[24][25][26][27][28]32,37,38 six in Brazil, [19][20][21][22][23]30 two in Denmark, 18,35 and one each in either Austria, 36 Australia, 31 Finland, 29 Japan, 33 or Spain. 34 For those studies in which data were available, [17][18][19][21][22][23][24][25][26][27][28][30][31][32][33][34][35][36][37][38] mean ± standard deviation (SD) ages were 68.1 ± 3.1 years in the resistance training groups (median = 67.7) and 67.5 ± 3.9 years in the control groups (median = 67.4).…”
Section: Data Sourcementioning
confidence: 99%
“…10 The characteristics of the included studies are described here in the Methods versus the Results section of the final manuscript because they were derived from the previous systematic review with meta-analysis. 10 Briefly, nine studies were conducted in the United States, 17,[24][25][26][27][28]32,37,38 six in Brazil, [19][20][21][22][23]30 two in Denmark, 18,35 and one each in either Austria, 36 Australia, 31 Finland, 29 Japan, 33 or Spain. 34 For those studies in which data were available, [17][18][19][21][22][23][24][25][26][27][28][30][31][32][33][34][35][36][37][38] mean ± standard deviation (SD) ages were 68.1 ± 3.1 years in the resistance training groups (median = 67.7) and 67.5 ± 3.9 years in the control groups (median = 67.4).…”
Section: Data Sourcementioning
confidence: 99%
“…Cardiovascular benefits have been described, as reducing arterial stiffness [63] and blood pressure [64]. RTP can also help to improve FC in older adults, a meta-analysis with 22 studies reported that within 24-week programs, there was a 2.57 ml/kg/min mean gain in VO2max, assessed by ET [65]. In heart failure patients, RTP achieved an improvement of muscle strength, quality of life, and FC [66].…”
Section: Resistance Training In Older Adultsmentioning
confidence: 99%
“…Physical exercise is widely recognized as a rst-line intervention strategy to combat obesity and its complications. Previous studies have shown that resistance exercise can enhance human metabolic function and improve cardiorespiratory tness in as little as 6 sessions consisting of < 12 min of exercise over two weeks (Gibala et al, 2006;Thomas et al, 2022). Intriguingly, despite its encouraging bene ts, clinical trials investigating the e cacy of exercise interventions have reported highly variable and inconsistent results (Timmons et al, 2011;Bouchard et al, 2012).…”
Section: Introductionmentioning
confidence: 99%